2022
DOI: 10.3390/diagnostics12010199
|View full text |Cite
|
Sign up to set email alerts
|

Gait Alterations in Adults after Ankle Fracture: A Systematic Review

Abstract: (1) Background: Ankle fracture results in pain, swelling, stiffness and strength reduction, leading to an altered biomechanical behavior of the joint during the gait cycle. Nevertheless, a common pattern of kinematic alterations has still not been defined. To this end, we analyzed the literature on instrumental gait assessment after ankle fracture, and its correlation with evaluator-based and patient-reported outcome measures. (2) Methods: We conducted a systematic search, according to the Preferred Reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…This data is important information for both the orthopedic provider and the primary care provider as they counsel patients throughout the rehabilitation process. Lack of attention paid to patient weight is concerning since postoperative patients are at risk of weight gain secondary to decreased activity levels caused by postoperative immobility, altered gait mechanics, pain, and posttraumatic osteoarthritis [26][27][28][29][30] . This study highlights the need for more research into the effects of orthopedic surgery on weight fluctuations after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data is important information for both the orthopedic provider and the primary care provider as they counsel patients throughout the rehabilitation process. Lack of attention paid to patient weight is concerning since postoperative patients are at risk of weight gain secondary to decreased activity levels caused by postoperative immobility, altered gait mechanics, pain, and posttraumatic osteoarthritis [26][27][28][29][30] . This study highlights the need for more research into the effects of orthopedic surgery on weight fluctuations after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a global health pandemic with significant economic and health consequences [3][4][5] . Compared to patients with a healthy body mass index , patients with a BMI in the overweight (BMI [25][26][27][28][29][30] and obese (BMI >30) categories have more comorbidities and are at much greater risk for health-related complications [6][7][8] . Despite the increasing prevalence of obesity in the United States (US), few studies have evaluated weight changes following orthopedic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…All gait variables were decreased in both the affected and unaffected ankles of the patient group. (17) One of the most significant changes in the comparison of previously injured extremity with non-injured extremity shows that patients still reduce the amount of weight transferred to their previously injured extremities, despite long follow-up periods. With the reduction of stance time and maximum load, less weight is placed on the fractured extremity in a shorter time.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding balance and fractures, ankle fracture primarily causes gait cycle alteration and unbalance. In this context, gait assessment might be useful in this condition, as described by Mirando et al [ 26 ] in a recent systematic review, including 12 studies, aiming to objectively characterize through gait analysis the alterations in walking. The authors found a reduction in step length, swing time, single support time, stride length, cadence, speed, and an earlier foot-off time in the affected side.…”
Section: Diagnostics In Bone Diseasesmentioning
confidence: 99%